Practical ethics - Singer, Peter, 1946- (Cambridge : Cambridge University Press, 2011)
For thirty years, Peter Singer's Practical Ethics has been the classic introduction to applied ethics. For this third edition, the author has revised and updated all the chapters and added a new chapter addressing climate change, one of the most important ethical challenges of our generation. Some of the questions discussed in this book concern our daily lives. Is it ethical to buy luxuries when others do not have enough to eat? Should we buy meat from intensively reared animals? Am I doing something wrong if my carbon footprint is above the global average? Other questions confront us as concerned citizens: equality and discrimination on the grounds of race or sex; abortion, the use of embryos for research and euthanasia; political violence and terrorism; and the preservation of our planet's environment. This book's lucid style and provocative arguments make it an ideal text for university courses and for anyone willing to think about how she or he ought to live.
About ethics -- Equality and its implications -- Equality for animals? -- What's wrong with killing? -- Taking life : animals -- Taking life : the embryo and fetus -- Taking life : humans -- Rich and poor -- Climate change -- The environment -- Civil disobedience, violence and terrorism -- Why act morally?
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Ethics; Social ethics